Patellar Instability. Issue 11 (28th November 2022) - Perry, Allison K.; Maheshwer, Bhargavi; DeFroda, Steven F.; Hevesi, Mario; Gursoy, Safa; Chahla, Jorge; Yanke, Adam
Abstract : ➢ Certain anatomic factors, such as patella alta, increased tibial tubercle-trochlear groove distance, rotational deformity, and trochlear dysplasia, are associated with an increased risk of recurrent patellar instability. ➢ The presence of a preoperative J-sign is predictive of recurrent instability after operative management. ➢ Isolated medial patellofemoral ligament reconstruction may be considered on an individualized basis, considering whether the patient has anatomic abnormalities such as valgus malalignment, trochlear dysplasia, or patella alta in addition to the patient activity level. ➢ More complex operative management (bony or cartilaginous procedures) should be considered in patients with recurrent instability, malalignment, and certain anatomic factors.